2016
DOI: 10.1158/0008-5472.can-15-2654
|View full text |Cite
|
Sign up to set email alerts
|

Ly6E/K Signaling to TGFβ Promotes Breast Cancer Progression, Immune Escape, and Drug Resistance

Abstract: Stem cell antigen Sca-1 is implicated in murine cancer stem cell biology and breast cancer models, but the role of its human homologues Ly6K and Ly6E in breast cancer are not established. Here we report increased expression of Ly6K/E in human breast cancer specimens correlates with poor overall survival, with an additional specific role for Ly6E in poor therapeutic outcomes. Increased expression of Ly6K/E also correlated with increased expression of the immune checkpoint molecules PDL1 and CTLA4, increased tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 49 publications
2
79
0
Order By: Relevance
“…Ubiquitination and N-glycosylation have known effects on the immunosuppressive activity of PD-L1 35. Also, increased expression of stem cell antigens Ly6K and Ly6E is reported to facilitate the activation and expression of cytokine-induced PD-L1, subsequently promoting drug resistance 36. The alimentary nutrient apigenin and its essential component luteolin have both been shown to indirectly inhibit interferon (IFN)-γ-induced PD-L1 expression via depression of signal transducer and activator of transcription (STAT) 1 phosphorylation, while not affecting constitutive PD-L1 31…”
Section: Tumor-related Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitination and N-glycosylation have known effects on the immunosuppressive activity of PD-L1 35. Also, increased expression of stem cell antigens Ly6K and Ly6E is reported to facilitate the activation and expression of cytokine-induced PD-L1, subsequently promoting drug resistance 36. The alimentary nutrient apigenin and its essential component luteolin have both been shown to indirectly inhibit interferon (IFN)-γ-induced PD-L1 expression via depression of signal transducer and activator of transcription (STAT) 1 phosphorylation, while not affecting constitutive PD-L1 31…”
Section: Tumor-related Immune Evasionmentioning
confidence: 99%
“…Tregs can protect CTC from immune attack, alleviate the killing capacity of CTLs, and trigger larger quantity of myeloid-derived suppressor cells (MDSCs) 33. Immune infiltration of Tregs is related to clinical prognosis,72 and can be augmented by Ly6E and Ly6K 36. The upregulation of GITR-related protein with Treg-inhibiting activity increases the proliferation, activation, and synthesis of cytokines 49.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…The potential mechanism was then analyzed. It has been previously shown that LY6E could downregulate tumor-suppressor proteins, including phosphatase with tensin homology (PTEN) [33], and E-Cadherin [34], thus promoting cell proliferation and invasion. In this study, we show that LY6E knockdown by LY6E siRNA3 increased expressions of PTEN (increase by 183.4%) and E-Cadherin (increase by 87.1%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LY6E is involved in cell signalling transduction, cell adhesion, immune regulation and drug resistance [21, 33, 34, 43]. It is over-expressed in human malignancies, including head and neck squamous cell carcinomas and lung, and oesophageal cancers [21, 33, 34, 43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation